Assessing the Effectiveness of a Combination of Online Applications in Teaching Indonesian Language to University Students in Madagascar - R. Hariyani Susanti (Politeknik Negeri Bengkalis, 2023)
The purpose of the study was to investigate the efficiency of teaching Indonesian to foreign students via an online platform. 10 university students from Madagascar University participated in the 1-month Indonesian language course that took place from September 12th to October 8th, 2022. Despite the limitations of the online learning setting, the students were eager to learn and took part in the program. The researchers utilized a combination of Zoom, a puzzle game, and a quizzing tool to support the learning process. A mixed method approach was employed to analyze the data collected. The aim of the study was to gauge the students' perceptions and attitudes towards the online Indonesian language learning process. The results indicate that the online Indonesian language learning approach that involved Zoom, the puzzle game, and the quizzing tool was effective in promoting satisfaction, comfort, and improvement in language skills among the majority of the students.